Understanding genocide : the social psychology of the Holocaust - Newman, Leonard S. 1961-; Erber, Ralph; ebrary, Inc (Oxford University Press, 2002)
When and why do groups target each other for extermination? How do seemingly normal people become participants in genocide? Why do some individuals come to the rescue of members of targeted groups, while others just passively observe their victimization? And how do perpetrators and bystanders later come to terms with the choices that they made? These questions have long vexed scholars and laypeople alike, and they have not decreased in urgency as we enter the twenty-first century. In this book--the first collection of essays representing social psychological perspectives on genocide and the Ho